Do U.S. marketing orders have much market power? An examination of the Almond Board of California - Crespi, John M. (2004)
This review tests the conventional wisdom that U.S. marketing orders act as profit-maximizing cartels. It analyzes the marketing order for U.S. almonds in both the domestic and export markets. Such a case study is relevant to all U.S. marketing orders because the size and scope of the U.S. almond industry and the authority granted to a board of producers by the almond marketing order would seem to be conducive to profit-maximizing cartel behavior. Nevertheless, the authors find that the market power exerted by the Almond Board of California is significantly less than would be expected from a profit-maximizing cartel.